IMPLEMENTASI NILAI DEMOKRASI DALAM INKLUSI POLITIK RAKYAT BERBASIS DIGITAL - Juantara, Bendi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Current global geopolitical, economic and digital hegemony has posed a serious threat to achieving national ideals and goals. In this context, there needs to be an attitude and action taken by a country to respond proactively and adaptively to develop strategic planning to maintain stability & sustainability in the future. Unfortunately, in facing this, internally Indonesia is still trapped by substantive challenges and obstacles. Starting from the leadership aspect, budget limitations, infrastructure, difficulties in collaboration between stakeholders, to the still low level of community awareness and participation. This research aims to examine opportunities for implementing democratic values ??in digital-based political inclusion of the people. The research method used is a descriptive approach with secondary data sources. Some of the findings from this research are that the idea of ??reforming the political sector (good political governance) is something important and a priority to be developed in the future. Implementation of people's political inclusion can be an antidote to the death of the flow of democratic development in representative political bodies. Digital media space can be used as an arena for implementing people's political inclusion. On the basis of an online platform, people can participate in discussions and share views, organize political movements, and voice demands to political leaders, as well as take part in public consultations